ApoE influences amyloid-β (Aβ) clearance despite minimal apoE/Aβ association in physiological conditions - Verghese, Philip B.; Castellano, Joseph M.; Garai, Kanchan; Wang, Yinong; Jiang, Hong; Shah, Aarti; Bu, Guojun; Frieden, Carl; Holtzman, David M. (Proceedings of the National Academy of Sciences - PNAS, 2013)
Apolipoprotein E gene (APOE) alleles may shift the onset of Alzheimer’s disease (AD) through apoE protein isoforms changing the probability of amyloid-β (Aβ) accumulation. It has been proposed that differential physical interactions of apoE isoforms with soluble Aβ (sAβ) in brain fluids influence the metabolism of Aβ, providing a mechanism to account for how APOE influences AD risk. In contrast, we provide clear evidence that apoE and sAβ interactions occur minimally in solution and in the cerebrospinal fluid of human subjects, producing apoE3 and apoE4 isoforms as assessed by multiple biochemical and analytical techniques. Despite minimal extracellular interactions with sAβ in fluid, we find that apoE isoforms regulate the metabolism of sAβ by astrocytes and in the interstitial fluid of mice that received apoE infusions during brain Aβ microdialysis. We find that a significant portion of apoE and sAβ compete for the low-density lipoprotein receptor-related protein 1 (LRP1)–dependent cellular uptake pathway in astrocytes, providing a mechanism to account for apoE’s regulation of sAβ metabolism despite minimal evidence of direct interactions in extracellular fluids. We propose that apoE influences sAβ metabolism not through direct binding to sAβ in solution but through its actions with other interacting receptors/transporters and cell surfaces. These results provide an alternative frame work for the mechanistic explanations on how apoE isoforms influence the risk of AD pathogenesis.